The Effect of Capital Structure on the Profitability of Oil Marketing Companies (OMCS) in Ghana - Okine, M.A. (University of Ghana, 2019)
The central objective of this study is to assess the effect of capital structure on performance of OMCs in Ghana. The data sample consists of six oil marketing companies that have been in continuous existence from 2010-2015. The study employed panel regression models to examine the relationship between capital structure and performance of OMCs in Ghana. The results of this study show that the analysis of leverage and firm performance relationship produces mixed outturns. The leverage has a positive relationship with return on equity but relates inversely with return on asset. These findings found support for both the bankruptcy cost and tax benefits arguments. The study results also suggest that the size of the firm has positive and significant effects on return on assets (ROA) and return on equity (ROE). The larger firms have easier access to external funds and are most likely able to meet their investment needs thus increasing their profitability. The results of the regression analysis show that the liquidity ratio produces negative effects on return on asset. This finding confirms the liquidity and profitability trade off theory.
MSc. Development Finance
Keywords: Capital Structure; Ownership; Ghana; Ghana; Marketing; Equity; Assets